A Risk Factor Study on Food Establishments in Kansas - Futrell, Crystal (My University, 2021)
The Centers for Disease Control and Prevention (CDC) estimate that foodborne illnesses affect 48 million people in the United States annually. These illnesses result in approximately 128,000 hospitalizations, 3,000 deaths, and an economic burden of more than $15.5 billion dollars—each year.¹ Most of these diseases are caused by pathogenic bacteria, viruses and parasites, but chemicals and toxins can also cause illness. ² Fortunately, foodborne illnesses are largely preventable, but in order to know how to prevent them, we need to understand where they originate. There are many sources where food can become contaminated and cause a foodborne illness outbreak, but according to the CDC’s 2017 Surveillance Report, the single food preparation setting that had over 64% of that year’s outbreaks were restaurants with the majority of that percentage being sit-down dining establishments.³ Now, did the restaurants receive contaminated food, or did the food become contaminated because of risky food handler practices? Both are likely possibilities, but CDC surveillance has identified five common practices in food preparation settings that most contribute to foodborne illness. These five areas are: ⁴ 1. Poor personal hygiene 2. Improper hot/cold holding temperatures 3. Improper cooking temperatures 4. Food from unsafe sources 5. Contaminated equipment/protection from cross contamination To assess their state’s enforcement of food safety practices and their management of the above five areas in food preparation settings, the Kansas Department of Agriculture (KDA) conducted a Risk Factor Study for the Food and Drug Administration (FDA). This study analyzed twenty-seven data points from their inspection reports that best connect to the above five food safety risk factors. These inspections are from restaurants, retail food stores, schools and satellite schools. The intent of this analysis was to analyze previously instated intervention strategies in those settings to assess their effectiveness while also detecting continued and/or additional food safety concerns that would inform potential intervention strategies. These potential interventions include: training, developing standard operating procedures, and utilizing different colored cutting boards for ready-to-eat foods. My task for this Integrated Learning Experience was to utilize the methods and concepts learned throughout my time as a K-State Master of Public Health (MPH) student to assist KDA with the analysis and development of reports for this Risk Factor Study. This paper is a summary of my findings.
Keywords: food safety; foodborne illness; food establishment; public health; KDA; inspection